The art of living well Cultural participation and well-being - Murtin, Fabrice (OECD Papers on Well-being and Inequalities, 2024)
This paper first presents a meta-analysis of the causal impact of cultural participation on well-being. The meta-analysis classifies the literature according to the strength of the evidence available and various types of cultural activities. Secondly, this paper uses data from time use surveys from Canada, France, Italy, the United Kingdom, and the United States to study individuals' emotional responses to a series of daily activities. This is then used as a basis for an empirical assessment of the drivers of time allocation across different activities, showing that expectations of future well-being are one of the reasons why individuals decide to engage in cultural activities. Furthermore, the model helps explain why cultural participation, in spite of being one of the most enjoyable human activities, is also the least undertaken. We show that heterogeneity of preferences results in a strong selection effect in available statistics